2020
DOI: 10.3390/ma13102239
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Changes in the Upper Airways after Rapid and Slow Maxillary Expansion in Growing Patients: A Case-Control Study

Abstract: The aim is to evaluate changes in the volume of the upper airways before and after slow maxillary expansion (SME) obtained with the flexible properties of a nickel titanium leaf spring and rapid maxillary expansion (RME) with a conventional Hyrax appliance in growing patients. The records of 1200 orthodontic patients undergoing maxillary expansion from 2018 to 2019 were analyzed; among these pre and post treatment CBCT scans of 22 patients (mean age 8.2 ± 0.6 years old) treated by SME were compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Depending on the spring chosen, these appliances can deliver a constant lateral force of 450 g or 900 g. It requires no compliance from the patients' parents, and when compared to conventional expanders, it was demonstrated to be less painful and able to provide a similar amount of expansion [27,28]. To date, the published data appear promising [29,30]. Therefore, the aim of the present observational retrospective study was to evaluate the dento-alveolar buccal tipping and the bone thickness changes around the upper first molars and deciduous primary molars (anchorage teeth) immediately after Leaf Expander treatment in patients with mixed dentition by means of CBCT scans.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the spring chosen, these appliances can deliver a constant lateral force of 450 g or 900 g. It requires no compliance from the patients' parents, and when compared to conventional expanders, it was demonstrated to be less painful and able to provide a similar amount of expansion [27,28]. To date, the published data appear promising [29,30]. Therefore, the aim of the present observational retrospective study was to evaluate the dento-alveolar buccal tipping and the bone thickness changes around the upper first molars and deciduous primary molars (anchorage teeth) immediately after Leaf Expander treatment in patients with mixed dentition by means of CBCT scans.…”
Section: Introductionmentioning
confidence: 99%
“…However, consensus regarding the impact that these therapeutic approaches might have on the airway has not been reached in the literature. Some studies have reported a favorable effect on the dimensions of the airway [ 7 , 8 , 9 , 10 ], while others have not confirmed such an effect [ 11 , 12 ]. A recent systematic review on the topic [ 13 ] reported that maxillary protraction can increase postpalatal and nasopharyngeal airway dimensions in growing skeletal class III subjects with maxillary retrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study demonstrated a medium OHI-s value of (1.68, 4.26) 2.97 ± 1.29 (DI: (1.01, 2.17)1.59 ± 0,58; confidence interval: (0.51, 2.05) 1.28 ± 0.77) [26]. Undoubtedly, the lower index values indicating the status of oral hygiene observed during the second appointment were strictly correlated to the hygienic instructions provide to the patients [27].…”
Section: Discussionmentioning
confidence: 89%